Evaluation of an online intervention for improving stroke survivors' health-related quality of life: A randomised controlled trial. - Ashleigh Guillaumier; Neil J Spratt; Michael Pollack; Amanda Baker; Parker Magin; Alyna Turner; Christopher Oldmeadow; Clare Collins; Robin Callister; Chris Levi; Andrew Searles; Simon Deeming; et al. (PLoS Medicine, 2022)
Background The aim of this trial was to evaluate the effectiveness of an online health behaviour change intervention-Prevent 2nd Stroke (P2S)-at improving health-related quality of life (HRQoL) amongst stroke survivors at 6 months of follow-up. Methods and findings A prospective, blinded-endpoint randomised controlled trial, with stroke survivors as the unit of randomisation, was conducted between March 2018 and November 2019. Adult stroke survivors between 6 and 36 months post-stroke with capacity to use the intervention (determined by a score of ≥4 on the Modified Rankin Scale) and who had access and willingness to use the internet were recruited via mail-out invitations from 1 national and 1 regional stroke registry. Participants completed baseline (n = 399) and 6-month follow-up (n = 356; 89%) outcome assessments via computer-assisted telephone interviewing (CATI). At baseline the sample had an average age of 66 years (SD 12), and 65% were male. Randomisation occurred at the end of the baseline survey; CATI assessors and independent statisticians were blind to group allocation. The intervention group received remote access for a 12-week period to the online-only P2S program (n = 199; n = 28 lost at follow-up). The control group were emailed and posted a list of internet addresses of generic health websites (n = 200; n = 15 lost at follow-up). The primary outcome was HRQoL as measured by the EuroQol Visual Analogue Scale (EQ-VAS; self-rated global health); the outcome was assessed for differences between treatment groups at follow-up, adjusting for baseline measures. Secondary outcomes were HRQoL as measured by the EQ-5D (descriptive health state), diet quality, physical activity, alcohol consumption, smoking status, mood, physical functioning, and independent living. All outcomes included the variable 'stroke event (stroke/transient ischaemic attack/other)' as a covariate, and analysis was intention-to-treat. At 6 months, median EQ-VAS HRQoL score was significantly higher in the intervention group than the control group (85 vs 80, difference 5, 95% CI 0.79-9.21, p = 0.020). The results were robust to the assumption the data were missing at random; however, the results were not robust to the assumption that the difference in HRQoL between those with complete versus missing data was at least 3 points. Significantly higher proportions of people in the intervention group reported no problems with personal care (OR 2.17, 95% CI 1.05-4.48, p = 0.0359) and usual activities (OR 1.66, 95% CI 1.06-2.60, p = 0.0256) than in the control group. There were no significant differences between groups on all other secondary outcomes. The main limitation of the study is that the sample comprises mostly 'well' stroke survivors with limited to no disability. Conclusions The P2S online healthy lifestyle program improved stroke survivors' self-reported global ratings of HRQoL (as measured by EQ-VAS) at 6-month follow-up. Online platforms represent a promising tool to engage and support some stroke survivors. Trial registration Australian New Zealand Clinical Trials Registry ACTRN12617001205325.